2014
DOI: 10.1021/am505723k
|View full text |Cite
|
Sign up to set email alerts
|

Cartilaginous Extracellular Matrix-Modified Chitosan Hydrogels for Cartilage Tissue Engineering

Abstract: Cartilaginous extracellular matrix (ECM) components such as type-II collagen (Col II) and chondroitin sulfate (CS) play a crucial role in chondrogenesis. However, direct clinical use of natural Col II or CS as scaffolds for cartilage tissue engineering is limited by their instability and rapid enzymatic degradation. Here, we investigate the incorporation of Col II and CS into injectable chitosan hydrogels designed to gel upon initiation by exposure to visible blue light (VBL) in the presence of riboflavin. Unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 71 publications
5
119
1
Order By: Relevance
“…Similarly, the safety and biocompatibility of hydrogels allow for their versatile applications in tissue engineering (36)(37)(38)66). Our photo-crosslinked chitosan hydrogel was degradable by lysozyme as confirmed in previous studies (41,42). Furthermore, prior studies have shown that PEG-based hydrogels have tunable degradation rates and are well tolerated (66,67), and the use of DMSO in our E2/ND/G platform was shown to have no biological effects or adverse toxicities.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, the safety and biocompatibility of hydrogels allow for their versatile applications in tissue engineering (36)(37)(38)66). Our photo-crosslinked chitosan hydrogel was degradable by lysozyme as confirmed in previous studies (41,42). Furthermore, prior studies have shown that PEG-based hydrogels have tunable degradation rates and are well tolerated (66,67), and the use of DMSO in our E2/ND/G platform was shown to have no biological effects or adverse toxicities.…”
Section: Discussionsupporting
confidence: 80%
“…Confirmation of sustained drug loading as well as release was assessed and visualized using E2/ND vials on a macroscopic scale at specific time points of 1 h, 2 h, 3 h, 4 h, 12 h, 48 h, 96 h, 120 h, 192 h, and 336 h. Drug and ND presence was visually confirmed at each time point, demonstrating the ability of the E2/ND/G to therapeutically address bone formation for a sustained period. The hydrogel properties such as gelation time, modulus, and cytotoxicity were confirmed as described in previous studies (41)(42)(43). Release of the E2 from NDs over time was quantified and confirmed using ELISA of the eluate (Fig.…”
Section: Resultssupporting
confidence: 74%
“…To increase the bioactivity of chitosan-based hydrogels, Choi et al developed a photocrosslinked chitosan hydrogel containing ECM constituents such as collagen II and chondroitin sulfate for cartilage repair. The hydrogel demonstrated the ability to promote chondrogenesis and increase cell-matrix interactions [113]. For repairing focal chondral injuries, a uniquely designed RGD-grafted N-methacrylated GC hydrogel was used to encapsulate ADSCs.…”
Section: Cartilage Regenerative Engineeringmentioning
confidence: 99%
“…22 Chitosan is another attractive base material for medical and pharmaceutical application due to its biocompatibility, biodegradability, and stimulation of cellular activities. 23 Despite a few examples of injectable hydrogels based on chondroitin sulfate and/or chitosan, the complicated synthetic procedures (e.g., photo-crosslinking 19,24 , enzymatic crosslinking 25 , grafting reaction 15,[26][27] and click chemistry 28 ) and the potential cytotoxicity of the agents used (e.g., photoinitiator, a local high concentration of H 2 O 2 in the peroxidases catalyzed crosslinking systems), impede their applications. Herein, we develop an injectable hydrogel using N-succinyl-chitosan and chondroitin sulfate through an inexpensive, facile and fast method.…”
Section: Introductionmentioning
confidence: 99%